(untitled) (Journal of the College of Basic Education, 2026)
Transport geography is one of the branches of human geography and is one of the economic branches of geography, as transport is one of the most important pillars of the economy of any country. Because roads are of great importance in transportation and because their efficiency is one of the basics of transportation movement, this research came to shed light on the most important quantitative measurement methods that are concerned with studying the land transportation network. In a simplified and illustrative way, since most transportation researchers suffer from knowing how to apply the basics of these methods. If the research starts from a main problem according to the following formulation (What is the efficiency of the main and secondary road network in Salah al-Din Governorate) Several secondary questions branched out from it, the most important of which is what is the result of the density of the road network in relation to the area and population? Is it possible to apply quantitative measurement methods in a detailed manner to all solution steps, given that most transportation geography researchers, especially graduate students, struggle to apply quantitative measurement methods in a way that achieves accurate results? The research concluded with a set of conclusions and proposals, the most important of which were: The turn indicator indicated that all roads in the network were highly straight, except for one road that had a low degree of straightness.